Anxiety in the Medically Ill: A Systematic Review of the Literature - Romanazzo, Sara; Mansueto, Giovanni; Cosci, Fiammetta (Frontiers in Psychiatry, 2022)
Background: Although anxiety is highly represented in the medically ill and its occurrence has relevant clinical implications, it often remains undetected and not properly treated. This systematic review aimed to report on anxiety, either symptom or disorder, in patients who suffer from a medical illness. Methods: English-language papers reporting on anxiety in medically ill adults were evaluated. PubMed, PsycINFO, Web Of Science, and Cochrane databases were systematically searched from inception to June 2021. Search term was “anxiety” combined using the Boolean ‘AND’ operator with “medically ill/chronic illness/illness/disorder/disease”. Risk of bias was assessed via the Joanna Briggs Institute (JBI) Critical Appraisal Tools – Checklist for Prevalence Studies. The PRISMA guidelines were followed. Results: Of 100,848 citations reviewed, 329 studies met inclusion criteria. Moderate or severe anxious symptoms were common among patients with cardiovascular, respiratory, central nervous system, gastrointestinal, genitourinary, endocrine, musculoskeletal system or connective tissue, dermatological diseases, cancer, AIDS and COVID-19 infections. The most common anxiety disorder was generalized anxiety disorder, observed among patients with cardiovascular, respiratory, central nervous system, dermatologic diseases, cancer, primary aldosteronism, amenorrhea, and COVID-19 infection. Panic disorder was described for cardiovascular, respiratory, dermatology diseases. Social anxiety was found for cardiovascular, respiratory, rheumatoid diseases. Specific phobias were relatively common in irritable bowel syndrome, gastroesophageal reflux, end-stage renal disease. Conclusion: Anxiety is a major challenge in medical settings. Recognition and proper assessment of anxiety in patients who suffer from a medical illness is necessary for an appropriate management. Future reviews are warranted in order also to clarify the causal and temporal relationship between anxiety and organic illness.